2014
DOI: 10.1038/nnano.2014.56
|View full text |Cite
|
Sign up to set email alerts
|

Generating electricity by moving a droplet of ionic liquid along graphene

Abstract: Since the early nineteenth century, it has been known that an electric potential can be generated by driving an ionic liquid through fine channels or holes under a pressure gradient. More recently, it has been reported that carbon nanotubes can generate a voltage when immersed in flowing liquids, but the exact origin of these observations is unclear, and generating electricity without a pressure gradient remains a challenge. Here, we show that a voltage of a few millivolts can be produced by moving a droplet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
532
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 546 publications
(553 citation statements)
references
References 28 publications
16
532
2
3
Order By: Relevance
“…This result was attributed to the absence of molecular reorientation on graphene with a chemically homogenous surface. Recently, Yin et al showed that the droplets of ionic liquid can easily slide on a graphene surface [86] and, in a much more interesting result, they found that the movement of the liquid−solid−gas three-phase boundary on a graphene surface can generate electricity [86,87]. All these results suggest that graphene is a promising material to construct efficient and intelligent channels for liquid flow.…”
Section: Frictional Interaction Between Liquid and 2d Materialsmentioning
confidence: 99%
“…This result was attributed to the absence of molecular reorientation on graphene with a chemically homogenous surface. Recently, Yin et al showed that the droplets of ionic liquid can easily slide on a graphene surface [86] and, in a much more interesting result, they found that the movement of the liquid−solid−gas three-phase boundary on a graphene surface can generate electricity [86,87]. All these results suggest that graphene is a promising material to construct efficient and intelligent channels for liquid flow.…”
Section: Frictional Interaction Between Liquid and 2d Materialsmentioning
confidence: 99%
“…Properties of graphene and h-BN manifest themselves in various important applications such as desalination, 1 water purification, 2 energy storage, 3 energy generation, [4][5][6][7][8] and catalysis. [9][10][11] For example, sizeable voltages have been measured from forming water salinity gradients across graphene sheets and nanotubes, [4][5][6][7] and Siria et al demonstrated that water flowing osmotically through a BN nanotube produces remarkably large electric currents. 8 This was attributed to the possible dissociation and adsorption of water on the interior of the nanotube which influences the dynamics inside the nanotube.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is often difficult to achieve such high electric fields by conventional dielectric gates. 1,2 Recently, extra-high electric fields are achieved by approaches such as Schottky junctions, 3,4 polar adsorbates 5,6 or ionic liquids [7][8][9][10][11][12] as dielectric gates in field-effect transistor devices. 13,14 For example, Xu et al 15 studied the modulation of grain boundary barriers in ZnMgO/ZnO/sapphire heterostructure by DI water and they found that the electronic conduction property of ZnO layer far beneath the surface could be switched from Ohmic to Schottky junction.…”
Section: Introductionmentioning
confidence: 99%